MENINGKATKAN HASIL BELAJAR SENI TARI DENGAN MENERAPKAN MODEL MAKE A MATCHPADA SISWA KELAS VIIIA SMPN - Rahmawati, Eka; Istiandini, Winda; Ismunandar, Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the aplication ofthe make a match model in improving studentsâ€™ results in Lumar District 1 VIIIA class. Bengkayang and discribing the studentsâ€™ learning desire in art learning, then applying the make-match model to the VIIIA students of the SMP Negeri this researchis the number of students who do not raech: the completeness of the class is based on VIIIA Which s mre then the old class. How is the application and learning outcomesÂ of students in Lumar Bengkayang Regenciy, the backround of the VIIIAThe State Junior High School by applying the make a match model to Bengkayang students in the theory that was anounced in dalah teani from belagar. The sen tan theory s important, including learning thematch method the research is an research, of descriptive analysis with a qualitative approach. The study was condusted in two cycles and each cycle has four stages, namely obsevation, and reflection. Data collection technques used are direct obsrevation, techniques, documentation. Keyword : Leaning Outcmes, Tari Learning, Match metho